MAKNA UMPAMA/UNGKAPAN MASYARAKAT PAKPAK - Nurelide Nfn (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Pakpak traditional expressions is a part of dispersed culture and passed on from generations traditionally among different social groups, whether in word speech forms with action even only behaviour or actions, such as proverbs, expressions, and puzzles. This research is aimed to describe Pakpaknese expression meanings. The methode used in this study is descriptive qualitative method. The findings described meaning in Pakpaknese traditional expressions based on folklore approach. Meanings in Pakpaknese traditional expressions are used in specific time, place, and circumstances. Such as tribes context, politeness, courage, health, family, and sincerity.